Influence of Hepatitis B immunization to prevent vertical transmission of Hep-B virus in infants bam from Hep-B positive mother - Liza Fitria; Hartono Gunardi; Arwin A. P. Akib (Indonesian Pediatric Society, 2010)
Background Hepatitis B is one of the most common infectious diseases worldv.ide. Indonesia has moderate-high endemicity for hepatitis B infection. Perinatal transmission increases the risk for chronic hepatitis B. Infants from HBsAg-positive mothers should receive hepatitis B immunoglobulin (HBIG) and vaccination within 12 hours of birth, but this practice is not routinely done in Indonesia due to financial constraints.Objectives To detennine the influence of Hep-B immunization on preventing Hepatitis B vertical transmission. Methods A descriptive cohort study was conducted from May 2009 - January 2010. Subjects were term infants born from HBsAg-positive mothers v.ith no history of HBIG administration. They had received complete hepatitis B immunization and 1 month after the last dose were evaluated for HBsAg and anti-HBs. Cord blood was also taken during labor to measure HBsAg.Results There were 22 infants born from HBsAg-positive mother who met the inclusion criteria. HBsAgwas positive in 6 of22 cord blood specimens. There were 15 infants who completed this study. One of 15 infants had positive HBsAg after completed hepatitis B immunization and 12 of 15 infants had protective level of anti-HBs. Effectiveness of hepatitis B immunization to prevent vertical transmission in this study was 70-90%.Conclusion Hepatitis B immunization can prevent vertical transmission of hepatitis B in infants born to mothers who are HBsAg-positive even without administration of HBIG.